(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Diabetic peripheral neuropathy is the damage of the nerves due to the uncontrolled diabetes. It can affect any of the neurons can affect any of the neurons. Diabetic distal symmetric sensory and sensorimotor polyneuropathy is the most prevalent type of diabetic neuropathy. The symptoms appear as sensory loss, first in the toes and progressively moving up the legs, fingers, and arms over time. Tingling sensation, Burning sensation, Deep aching pain are other related symptoms. A patient age 54 years with diabetes for past 15 years, hypertension, dyslipidemia, complains of burning sensation of both feet (right>left), numbness, pricking pain, unsteadiness while walking, brownish red discolouration of both lower limbs. The symptoms were gradual in onset. Nerve Conduction Study showed axonal type of motor and sensory affecting peroneal nerve neuropathy. He admitted in Vaidyaratnam Ayurveda College Hospital, done Vibrotherm Neuropathy Analyzer and revealed small and large fibre neuropathy with severe loss of sensations. The main intention of the study is to improve the quality of life of the patient by reducing the symptoms that is disturbing his day today routine. Patient given with anti diabetic Ayurvedic formulations internally. Externally Rookshana, Vatahara, Brimhana treatments were done. After the treatment, Michigan neuropathy screening instrument, diabetic Neuropathy symptom score, Toronto clinical scoring system score were reduced. Neuropathy Analyzer showed mild to moderate loss of sensation. By adopting Prameha hara chikitsa coupled with Vata vyadhihara chikitsa, complications of diabetes can be managed. It is important to focus on diet and regimen since diabetes is a lifestyle disorder and, in ayurveda it is considered as an Anushangi Vyadhi.